2022
DOI: 10.1186/s40634-022-00485-9
|View full text |Cite
|
Sign up to set email alerts
|

Tourniquet use in total knee arthroplasty and the risk of infection: a meta-analysis of randomised controlled trials

Abstract: Purpose The intra-operative use of tourniquets during Total Knee Arthroplasty (TKA) is common practice. The advantages of tourniquet use include decreased operating time and the creation of a bloodless visualisation field. However, tourniquet use has recently been linked with increased post-operative pain, reduced range of motion, and slower functional recovery. Importantly, there is limited evidence of the effect of tourniquet use on infection risk. The purpose of this systematic review and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that attitudes of orthopedic surgeons towards using PTs to prepare the operating field are mixed, with many concerns related to the higher risk of infection and longer hospital stay [ 24 , 25 ]. This study included a wider range of medical personnel, such as orthopedic nurses (31.5%) or operating room nurses (19.9%), and, most likely because of that, attitudes were predominantly positive.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that attitudes of orthopedic surgeons towards using PTs to prepare the operating field are mixed, with many concerns related to the higher risk of infection and longer hospital stay [ 24 , 25 ]. This study included a wider range of medical personnel, such as orthopedic nurses (31.5%) or operating room nurses (19.9%), and, most likely because of that, attitudes were predominantly positive.…”
Section: Discussionmentioning
confidence: 99%
“…Documentation on the use of interim antimicrobials was often lacking, such as the type of antibiotics given, the length of the course, and the route of administration, as well as details of the antibiotics loaded into the cement spacers, so these was not included in the final analysis. There was also variable documentation of the use of intraoperative tourniquet, so despite its previously recorded association with an increased risk of infection, 29 this was not included in the final data set. The retrospective nature design, however, meant that the data recorded in real time was done so without bias and with no influence from the current study.…”
Section: Discussionmentioning
confidence: 99%
“…These strict bleeding-control procedures help to minimize postoperative swelling due to hemorrhage, without an indwelling drain ( Table 2 ). As for OWHTO 10 or TKA, 11 the safe nontourniquet procedure may decrease the intraoperative/perioperative risks of complications such as bleeding, hematoma, or infection and may enhance postoperative recovery.…”
Section: Discussionmentioning
confidence: 99%